Emergence patterns of locally novel plant communities driven by past climate change and modern anthropogenic impacts. (11th May 2022) - Staples, Timothy L.; Kiessling, Wolfgang; Pandolfi, John M.
Abstract: Anthropogenic disturbance and climate change can result in dramatic increases in the emergence of new, ecologically novel, communities of organisms. We used a standardised framework to detect local novel communities in 2135 pollen time series over the last 25, 000 years. Eight thousand years of post‐glacial warming coincided with a threefold increase in local novel community emergence relative to glacial estimates. Novel communities emerged predominantly at high latitudes and were linked to global and local temperature change across multi‐millennial time intervals. In contrast, emergence of locally novel communities in the last 200 years, although already on par with glacial retreat estimates, occurred at midlatitudes and near high human population densities. Anthropogenic warming does not appear to be strongly associated with modern local novel communities, but may drive widespread emergence in the future, with legacy effects for millennia after warming abates. Abstract : Eight thousand years of post‐glacial warming coincided with a threefold increase in how often locally new, ecologically novel, communities emerged, relative to glacial estimates, predominantly at high latitudes and with multi‐millennial time lags. In contrast, emergence of locally novel communities in the last 200 years, although already on par with glacial retreat estimates, occurred at midlatitudes and near high human population densities. Anthropogenic warming does not appear to be strongly associated with modern local novel communities, but may drive widespread emergence in the future, with legacy effects for millennia after warming abates.